The First Records of Prince Vladimir in Sources - Đekić, Đorđe (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The paper attempts to answer the question of the first records of Prince Vladimir in historical sources. Up to now it has been considered that he was first mentioned in the work “A Synopsis of Byzantine History” by John Skylitzes. However, Henri Grégoire and Raoul De Keyser indicate that the prince was mentioned in “The Song of Roland” (“La Chanson de Roland”) as rei flurit, i.e., as the Blessed King. This epic originates from the spring of 1085 in Salerno, which was under the Norman rule at the time. This author agrees and supports the thesis by identifying a great number of concepts which refer to the Balkans (geographically, ethnically). It is believed that the Normans obtained information about the Balkans and Prince Vladimir while they held Dyrrhachium from 1081 to 1085.